Peace is a practice : an invitation to breathe deep and find a new rhythm for life - Nichols, Morgan Harper, 1990- (Zondervan, 2022)
"In today's fast-paced and chaotic world, popular Instagram poet and artist Morgan Harper Nichols has created a beautiful new book to remind us all that peace is a practice--one that will guide you to find stillness and awareness within your mind, heart, body, and soul despite the challenges of the here and now"--